A percepção dos atores do sistema de inovação paraibano sobre o papel da Universidade Federal da Paraíba - Ribeiro , Fabiano de Moura (2017)
In the current context, innovation systems are the main mechanism for transforming knowledge into economic valuation and improvement of the population quality of life, having strategic relevance for public policies of the State. From this perspective, most researchers consider the Brazilian Innovation System inefficient and disjointed. In order to contribute to the development of the Innovation System and, consequently, to the development of the state of Paraíba, universities presents themselves as actors whose peculiarities are capable of fostering this purpose. In this sense, this dissertation intends to answer the following research problem: How do the structure and organization of the Federal University of Paraíba (UFPB) articulate with the actors of the Innovation System of Paraíba (SPI)? In order to answer this question, the present research objected to analyze the structure and organization of the Federal University of Paraíba (UFPB) in its relations with the SIP. This research is characterized as a descriptive research, with qualitative approach, having case study as investigation method. In order to achieve the desired results, was used documentary research, interview and application of structured survey as data collection technique. Referring to data analysis, analysis of content was chosen. The aim of this study is to contribute to the improvement of the structure and organization of UFPB, in particular with regard to the Development Institute of Paraíba (IDEP - UFPB) and the UFPB Agency of Technological Innovation (INOVA - UFPB), in order to leverage the leading role aimed at promoting, in local and regional level, economic and social development inherent to the institution. In this context, the research concluded that there is a convergence of diagnostics about the main problems that affect the interactions of the UFPB with the actors in the SIP: The inadequate form of planning as well as the lack of incentive, interest and teaching motivation for activities of education, research and extension focused on the socioeconomic needs of the State of Paraíba.